Evaluation of forage yield and quality of sorghum, sudangrass and pearl millet cultivars in Manawatu : a thesis presented in partial fulfilment of the requirements for the degree of Master Agricultural Science in Agronomy at Massey University, Palmerston North, New Zealand - Silungwe, Davison (Massey University, 2011)
Sorghum, sudangrass and pearl millet are versatile summer forages which are able to be grazed or conserved as silage; however there is little recently published information on the performance of these crops in New Zealand. A trial was carried out at Massey University, Palmerston North, in order to compare forage yields, forage quality, crop morphology and seed quality of four sorghum x sudangrass hybrids (Pac 8421, Pac 8423, Pacific BMR and Bettagraze), two sudangrass (Superdan 2 and Sprint), one sweet sorghum (Sugargraze); and one pearl millet (Nutrifeed) cultivars, sown on the 8 and 21 December 2009. Two harvests were taken at approximately 100 cm plant height, leaving a residual of 15 cm. Nutritive values of the whole plant: crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), metabolisable energy (ME), and soluble sugars and starch (SSS) were determined, using near infrared reflectance (NIR). Accelerating ageing was used to assess seed vigour. Yields were significantly (P = 0.005) affected by plant date; mean yield for the 2nd plant date (11,356 kg DM/ha) was significantly lower than the 1st, (12,792 kg DM/ha). Pac 8423 (13,953 kg DM/ha), Sugargraze (13,262 kg DM/ha), Bettagraze (12,704 kg DM/ha) and Sprint (12,426 kg DM/ha), were the highest yielding group. There was a significant interaction (P<0.0001) between sowing date and cultivar, for yield at the second harvest; cultivar differences for the first sowing date were larger than that for the second, which suffered more from cool autumn temperatures. Crude protein ranged from 10.3 to 18%, NDF 57.2 to 65.2%, ADF 32.9 to 35.5%, ME 10.1 to 11 MJ/kg DM and SSS 1.2 to13.9%. CP and ME were negatively associated with plant height and yield, whilst CP was strongly and positively related to ME. Despite late sowing, most cultivars achieved high yields of relatively high quality forage. Significant differences amongst cultivars were observed. New cultivars displayed the potential to increase forage yield.
Keywords: Forage plants; Forage yield; Sorghum; Sudan grass; Pearl millet; Manawatu